(untitled) (Quest Journal of Management and Social Sciences, 2019)
Background: Contemporary organizations, more importantly, tourism and hospitality sectors, are heavily based on knowledge intensive dimensions. As they are emerging industries, and these sectors face fierce competition and strive for modernization of their business activities. However, the aging workforce in these industries poses huge challenges for the process of modernization. Organizations in these sectors do not follow knowledge management mechanism. As the importance of knowledge management is not well materialized, a comprehensive study is required to understand the grounded reality based on current need for practicing knowledge management in these sectors. Objectives: This study is conducted to identify various dimensions of knowledge management in tourism and hospitality sectors based on literature survey and to suggest managerial implications for managing knowledge in tourism and hospitality enterprises. Methods: within the framework of qualitative research, this study uses guided literature reviews, seminar discourses and general observation for collecting the data and analysis. Findings: This study has identified several dimensions that show shift of paradigm in knowledge management highlighting the importance of knowledge management in tourism enterprises. The study explores tourism entrepreneur’s awareness level of knowledge management. Informed with the related theories of knowledge management, the study explores measures for achieving sustainable tourism development through effective knowledge management. Conclusions: The study indicates that in order to advanced performance of these sectors, the owners and tourism entrepreneurs strategically require implementing the principles of knowledge management effectively. Implications: This paper may serve as instrumental as it attempts to analyze awareness level of tourism entrepreneurs on knowledge management providing evidences for its enhancement and development in Nepal.